2019
DOI: 10.1186/s40623-019-1095-6
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional S-wave attenuation structure in and around source area of the 2018 Hokkaido Eastern Iburi Earthquake, Japan

Abstract: We investigate S-wave attenuation (Qs) structure in and around Hokkaido, Japan, including the source area of the 2018 Hokkaido Eastern Iburi Earthquake (M 6.7) and its aftershocks. From the strong-motion seismograms recorded in the nationwide seismograph network in Japan, we compute spectrum amplitude at 1-10 Hz with every 1 Hz and then estimate Qs structure by adopting tomographic inversion technique. The obtained Qs structure suggests that lateral variations of Qs are remarkably formed in the study areas. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Fujiwara et al [19] identified and analyzed the surface displacements associated with earthquakes. Nakamura et al [20] investigated the S-wave attenuation (Qs) structure in and around Hokkaido, Japan, including a consideration of the source area of the earthquake and its aftershocks. Fukuda et al [21] analyzed the sleep pattern data of junior high school students on the night of a blackout after an earthquake, comparing their sleep to a normal night.…”
Section: Introductionmentioning
confidence: 99%
“…Fujiwara et al [19] identified and analyzed the surface displacements associated with earthquakes. Nakamura et al [20] investigated the S-wave attenuation (Qs) structure in and around Hokkaido, Japan, including a consideration of the source area of the earthquake and its aftershocks. Fukuda et al [21] analyzed the sleep pattern data of junior high school students on the night of a blackout after an earthquake, comparing their sleep to a normal night.…”
Section: Introductionmentioning
confidence: 99%
“…However, obtaining the depth profile of the 𝑄 −1 -structure is essential for adequately understanding this effect . Previous studies have estimated 𝑄-values that vary with depth (Hough & Anderson, 1988;Lin and Jordan, 2018;Wang et al, 2023), horizontally (Eulenfeld & Wegler, 2017 ;Prudencio et al, 2018 ), and in three dimensions (Eberhart-Phillips, 2005;Hauksson & Shearer, 2006;Nakajima & Matsuzawa, 2017;Nakamura & Shiina, 2019) , with various assumptions . However, few studies have examined the depth variation of the 𝑄 −1 -structure within the crust in detail given that most available data are far from the sources (>15 km).…”
Section: Introductionmentioning
confidence: 99%